Validation and evaluation of the psychometric properties of bangla nine-item Internet Disorder Scale–Short Form. Issue 4 (6th August 2020) - Saiful Islam, Md.; Rahman, Md. Estiar; Moonajilin, Mst. Sabrina; Griffiths, Mark D.
Abstract: Online activities such as online gaming and social media use have become very popular and for most individuals, engagement in such activities is highly enjoyable. However, for a small minority of individuals, such behaviors can lead to problematic internet use. There are many screening instruments that assess problematic internet use including the nine-item Internet Disorder Scale-Short-Form (IDS9-SF). The present study translated the IDS9-SF into Bangla and investigated its psychometric properties. The sample comprised 534 adolescents aged 13 to 18 years (61.0% male; mean age 15.7 years (SD = 1.5) from selected schools (secondary and higher secondary) in Dhaka City. The study included confirmatory factor analysis, Cronbach's alpha, and item-total correlation. Results demonstrated that the Bangla IDS9-SF had very good internal validity (Cronbach's alpha = .82), and that IDS score was positively and significantly correlated with scores on depression and anxiety scales. A confirmatory factor analysis showed the model had an excellent fit to the data. Therefore, the Bangla IDS9-SF appears to be a valid and reliable instrument that may be employed in further research on problematic internet use in Bangladesh.